2021
DOI: 10.3390/plants10091956
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Enzymatic Characterization of Flavonoid 3′-Hydroxylase of Malus × domestica

Abstract: Malus × domestica (apple) accumulates particularly high amounts of dihydrochalcones in various tissues, with phloridzin (phloretin 2′-O-glucoside) being prevalent, although small amounts of 3-hydroxyphloretin and 3-hydroxyphloridzin are also constitutively present. The latter was shown to correlate with increased disease resistance of transgenic M. × domestica plants. Two types of enzymes could be involved in 3-hydroxylation of dihydrochalcones: polyphenol oxidases or the flavonoid 3′-hydroxylase (F3′H), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Domesticated apple lines overexpressing CsC3H resulted in the production of 3hydroxyphloridzin, which correlated with reduced susceptibility to apple scab and fire blight, suggesting a beneficial role of 3hydroxylated DHCs (Hutabarat et al, 2016). A recent study attempted to discover genes involved in this key step of sieboldin biosynthesis, although the genes F3′HI and F3′HII cloned and characterised from M. × domestica genome did not accept phloretin, leading the authors to conclude that F3′Hs identified were unlikely involved in the 3-hydroxylation towards sieboldin biosynthesis (Weissensteiner et al, 2021). F3′HI and F3′ HII, however, accepted naringenin, dihydrokaempferol and kaempferol, indicating a role in the well-studied 3′-hydroxylation of the B ring of flavonoids.…”
Section: Functional Characterisation Of 3hydroxylase Involved In the ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Domesticated apple lines overexpressing CsC3H resulted in the production of 3hydroxyphloridzin, which correlated with reduced susceptibility to apple scab and fire blight, suggesting a beneficial role of 3hydroxylated DHCs (Hutabarat et al, 2016). A recent study attempted to discover genes involved in this key step of sieboldin biosynthesis, although the genes F3′HI and F3′HII cloned and characterised from M. × domestica genome did not accept phloretin, leading the authors to conclude that F3′Hs identified were unlikely involved in the 3-hydroxylation towards sieboldin biosynthesis (Weissensteiner et al, 2021). F3′HI and F3′ HII, however, accepted naringenin, dihydrokaempferol and kaempferol, indicating a role in the well-studied 3′-hydroxylation of the B ring of flavonoids.…”
Section: Functional Characterisation Of 3hydroxylase Involved In the ...mentioning
confidence: 99%
“…Although the glycosylation of 3-hydroxyphloretin can be carried out at least by PGT2 to produce sieboldin in vitro (Wang et al, 2020), the first committed step to 3hydroxyphloretin has not been yet identified. To date, the only attempt to identify genes involved in this step resulted in the characterisation of two flavonoid 3′-hydroxylases from M. × domestica (F3′HI and F3′HII), which did not accept phloretin and therefore unlikely to be involved in its 3-hydroxylation (Weissensteiner et al, 2021). In this study, we aimed to identify candidate genes that may account for the 3-hydroxylation of phloretin, that could be involved in DHC formation of wild Malus species.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one can conclude that CH3H is a specialized F3′H as it exhibits an additional functionality compared to F3′H. Furthermore, it was shown that apple plants overexpressing Cs CH3H exhibited an in increased level of 3-hydroxyphloretin 15 , while the in vitro assays of apple F3′Hs did not show dihydrochalcone hydroxylation activity 16 , 17 .…”
Section: Introductionmentioning
confidence: 98%
“…Selective hydroxylation of aromatic compounds is still a challenging chemical reaction in synthetic chemistry and has been gaining increasing interest in recent years, especially due to the use of hydroxylated aromatic compounds in the pharmaceutical industry [5]. The use of isolated enzymes or whole cells for biocatalytic oxygen transfer is an environmental friendly, inexpensive and efficient way of targeted hydroxylation [2,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the hydroxylation of flavonoids has not been widely studied to date. Recent literature reports give examples of hydroxylation at C-3ʹ, and C-6 positions mediated by enzymes belonging to the cytochrome P-450 monooxygenase group, requiring interaction with at least one oxidoreductase [8,[19][20][21][22][23]. A few examples of flavonoid hydroxylation at the C-8 position have been also described [21,24].…”
Section: Introductionmentioning
confidence: 99%